RNA interference tools for the western flower thrips, Frankliniella occidentalis. (May 2015) - Badillo-Vargas, Ismael E.; Rotenberg, Dorith; Schneweis, Brandi A.; Whitfield, Anna E.
Graphical abstract: Highlights: Prior to our study, successful RNAi had not been described in thrips. V-ATPase-B dsRNA injection of thrips triggered a reduction in the target transcript. This transcript silencing also resulted in a reduction in protein expression. RNAi of V-ATPase-B resulted in decreased survival and fertility of female thrips. RNAi is a functional process in thrips and can be used for functional genomic assays. Abstract: The insect order Thysanoptera is exclusively comprised of small insects commonly known as thrips. The western flower thrips, Frankliniella occidentalis, is an economically important pest amongst thysanopterans due to extensive feeding damage and tospovirus transmission to hundreds of plant species worldwide. Geographically-distinct populations of F. occidentalis have developed resistance against many types of traditional chemical insecticides, and as such, management of thrips and tospoviruses are a persistent challenge in agriculture. Molecular methods for defining the role(s) of specific genes in thrips–tospovirus interactions and for assessing their potential as gene targets in thrips management strategies is currently lacking. The goal of this work was to develop an RNA interference (RNAi) tool that enables functional genomic assays and to evaluate RNAi for its potential as a biologically-based approach for controlling F. occidentalis . Using a microinjection system, we delivered double-stranded RNA (dsRNA) directly to the hemocoel of female thrips to target the vacuolar ATP synthase subunit B ( V-ATPase-B ) gene of F. occidentalis . Gene expression analysis using real-time quantitative reverse transcriptase-PCR (qRT-PCR) revealed significant reductions of V-ATPase-B transcripts at 2 and 3 days post-injection (dpi) with dsRNA of V-ATPase-B compared to injection with dsRNA of GFP . Furthermore, the effect of knockdown of the V-ATPase-B gene in females at these two time points was mirrored by the decreased abundance of V-ATPase-B protein as determined by quantitative analysis of Western blots. Reduction in V-ATPase-B expression in thrips resulted in increased female mortality and reduced fertility, i.e., number of viable offspring produced. Survivorship decreased significantly by six dpi compared to the dsRNA- GFP control group, which continued decreasing significantly until the end of the bioassay. Surviving female thrips injected with dsRNA- V-ATPase-B produced significantly fewer offspring compared to those in the dsRNA- GFP control group. Our findings indicate that an RNAi-based strategy to study gene function in thrips is feasible, can result in quantifiable phenotypes, and provides a much-needed tool for investigating the molecular mechanisms of thrips–tospovirus interactions. To our knowledge, this represents the first report of RNAi for any member of the insect order Thysanoptera and demonstrates the potential for translational research in the area of thrips pest control.